Interaction between p53 N terminus and core domain regulates specific and nonspecific DNA binding - He, Fan (Proc Natl Acad Sci U S A, 2019)
The p53 tumor suppressor is a sequence-specific DNA binding protein that activates gene transcription to regulate cell survival and proliferation. Dynamic control of p53 degradation and DNA binding in response to stress signals are critical for tumor suppression. The p53 N terminus (NT) contains two transactivation domains (TAD1 and TAD2), a proline-rich region (PRR), and multiple phosphorylation sites. Previous work revealed the p53 NT reduced DNA binding in vitro. Here, we show that TAD2 and the PRR inhibit DNA binding by directly interacting with the sequence-specific DNA binding domain (DBD). NMR spectroscopy revealed that TAD2 and the PRR interact with the DBD at or near the DNA binding surface, possibly acting as a nucleic acid mimetic to competitively block DNA binding. In vitro and in vivo DNA binding analyses showed that the NT reduced p53 DNA binding affinity but improved the ability of p53 to distinguish between specific and nonspecific sequences. MDMX inhibits p53 binding to specific target promoters but stimulates binding to nonspecific chromatin sites. The results suggest that the p53 NT regulates the affinity and specificity of DNA binding by the DBD. The p53 NT-interacting proteins and posttranslational modifications may regulate DNA binding, partly by modulating the NT–DBD interaction.